Validity Of The Development Of Digital Comics-Based Learning Media For Learning Writing Short Stories At High School - Ririn Oktavia; Hasnah Faizah AR; Silvia Permatasari (Publikasiku, 2024)
We would like to express our gratitude to the presence of God Almighty for all His mercy and grace so that this research can be completed well. This research is entitled “The Validity of Developing Digital Comic-Based Learning Media for Learning to Write Short Stories in High Schools”. This research aims to determine the results of the validity or relevance/feasibility of digital comic-based learning media. Product validity is seen from the assessment of material experts, language experts and media experts. This type of research Research and development which refers to the ADDIE development model which consists of 5 steps, namely Analysis (analysis),Design (design/planning), Development (development), Implementation (Implementation), and Evaluation(evaluation). Data used in this researchis quantitative and qualitative data. The research results show that the average value of the validity test calculation is 94% for material experts, 81% for language experts and 91% for media experts. From matter This means that digital comic-based learning media for writing short stories is very relevant and very relevant potential to be used in the learning process, especially short story material so that you can stimulating and improve students' short story writing abilities.